P-(S. P) Submodules and C1(Extending) Modules - Talak, Abdulsalam F.; Abed, Majid Mohammed (Journal of physics. Conference series, 2021)
In this work, we study C 1 -(extending) module M through the sub-module of M which have two properties namely prime and semi-prime (P. (S. P)). Indeed these properties with another concept like fully invariant of any sub-modules explain the main objective of this study. Also heart submodule of a module M and the socle of M are studied with fully invariant property to obtain the same objective.